States at Work Dynamics of African Bureaucracies - de Sardan, Jean-Pierre Olivier; Bierschenk, Thomas (Brill, 2020)
States at Work explores the mundane practices of state-making in Africa by focussing on the daily functioning of public services and the practices of civil servants. Adopting mainly an ethnographic approach as a basis for theorizing, the authors deal with topics including: bureaucratic cultures and practical norms, operational routines in offices, career patterns and modes of appointment; how bureaucrats themselves perceive and deliver goods and services and interact with service users; the accumulation of public administration reforms and how the different bureaucratic corps react to the 'good governance' discourse and new public management policies; the consequences of these reforms for the daily working of state bureaucracies and for the civil servants' identities and modes of accountability; and the space that exists for bottom-up micro-reforms that build on local innovations or informal arrangements.